STUDI TENTANG MINAT UNTUK BEKERJA SISWA KELAS XII JURUSAN TEKNIK BANGUNAN SMK NEGERI 1 TANJUNG RAYA KABUPATEN AGAM - 1690-1704 , M.Havids (Universitas Negeri Padang, 2016)
ABSTRACT SMK 1 Tanjung Raya Agam Regency is one of the vocational educational institution that has a job to prepare the students with encouraged them with knowledge and skill to be able to work based on their own competence. Based on the graduate report data of the SMK 1Tanjung Raya Agam, there’s only a few number of its graduates that continue to work. To know the student’s interest to work, The Study about The Students Interest to Work of XII grade Civil Engineering of SMK 1 Tanjung Raya Agam.This research is using a descriptive method. The population are student’s of XII grade Civil Engineering on January-June 2016 term. The data that has been using to collect by questionnaire. While the data analyzing method that has been using are descriptive statistics analyzing method with percentage calculation.The result of this research reveals three indicators of Interest aspect that are cognitive, afective, and psicomotoric with a high category. As a whole, the Interest to work for the XII grade Civil Engineering SMK 1 Tanjung Raya students highly. Keywords: interest, interest aspect, career, SMK